Effects of abiraterone acetate plus prednisone on bone turnover markers in chemotherapy-naïve mCRPC patients after ADT failure: A prospective analysis of the italian real-world study ABITUDE - Santini, Daniele (J Bone Oncol, 2020)
BACKGROUND: Bone remodeling is disrupted in metastatic disease, which affects > 70% of metastatic castration-resistant prostate cancer (mCRPC) patients. As a result, abnormal levels of specific bone turnover biomarkers (BTMs) are released. In this prospective ancillary analysis of the Italian real-world study ABITUDE, four markers were measured during abiraterone acetate plus prednisone (AAP) treatment in chemotherapy-naïve mCRPC men failing androgen-deprivation therapy. METHODS: Patients were enrolled if a blood sample was obtained before the first administration of abiraterone (baseline); ad-hoc blood samples were withdrawn during routine tests after 3, 6, and 12 months. A centralized lab measured bone alkaline phosphatase (BALP, osteoblast activity marker), type-I collagen-C-telopeptide (CTX-1, bone resorption marker), parathyroid hormone (PTH) and vitamin D (vitD). At each time point, intra-patient variations vs baseline were compared by the signed-rank test (statistical significance: P-value < 0.05). RESULTS: Of 481 patients enrolled in ABITUDE, 186 (median age: 76 [range: 53–93] years) met the substudy criteria: 74.7% had bone metastases, 11.8% were on bone-targeted therapies (BTT) and 14.0% on vitD supplementation. BALP decreased significantly at month 6 (P = 0.0010) and 12 (P < 0.0001) and CTX-1 at month 6 (P = 0.0028); PTH increased at month 3 (P < 0.0001); no significant difference in vitD levels was observed. Similar findings were observed in BTT-untreated patients. The reduction in BALP and CTX-1 levels was more pronounced in patients with than without bone metastases; in the latter group, no significant variation in BALP and CTX-1 levels was observed. CONCLUSIONS: AAP seems to exert an effect on the microenvironment of metastatic but not of normal bone, which likely contributes to its antitumoral activity.